Who leaves the city? the influence of ethnic segregation and family ties - Aslan Zorlu (Institute for the Study of Labor (IZA), 2008)
In the last three decades, the population of Amsterdam has been 'coloured' due to immigration flows from abroad and a low outflow rate among these immigrants and their descendants. The question is to what extent differences in spatial mobility behaviour of migrants and natives are generated by neighbourhood characteristics - among which the level of ethnic segregation - and family ties? This article examines spatial mobility process of Amsterdam population using administrative individual data covering the entire population of the city. The analysis shows that Caribbean (Surinamese and Antillean) migrants have a higher probability of moving to suburbs while Moroccans and Turks tend to rearrange themselves within the city. The estimates reveal that neighbourhood 'quality' has only a modest impact on the probability of moving while family ties significantly hamper the out-mobility of all individuals. The impact of family ties is the largest for Turkish and Moroccan migrants.
Keywords: J1; 300; Migrants; residential mobility; family ties; Migranten; Einwanderung; Wohnstandort; Segregation; Soziale Beziehungen; Familiensoziologie; Amsterdam (Region)